The Higher Education Students Experience with Technology - Sihombing, Haeryip (Asian-Transactions org., 2011)
This study is to explore the students’ preferences and familiarities towards technology and the use of technology tools for their daily lives related to academic tasks. Particularly, on the higher education students’ access to technology-based tools and their preferences for a wide range of established and emerging technologies. Through the survey conducted on the first semester students of Polytechnic Merlimau Melaka, the results show and indicate that many of them are tech-savvy, even beyond the common technology applied. In the pattern of access and use of a range of other technologies (which are high-tech applications), a considerable variation is prevalent. The findings discussed is close to the notions of ‘Digital Natives’ of Prensky’s reference, in which the implications for harnessing available technologies in order to support teaching and learning in higher education are also comprehensively reviewed in this paper.